Millennial tourists’ perception on Gedhe Mataram mosque as religious tourism site - Uystka Hikmatul Kamiliyah NH (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to analyze the perception of millennial tourists towards Gedhe Mataram mosque in terms of five components: attractions, amenities, accessibilities, human resources, and prices.Method — This qualitative descriptive research involves multiple millennial informants. Observation at Gedhe Mataram mosque area, interviews with 16 millennial visitors, and field documentation comprise the data gathering methods. A random sample of millennial visitors visiting Gedhe Mataram mosque area was selected using the informant selection technique. All discovered data is examined using the Spradley model.Result — The results indicated that Gedhe Mataram mosque area's overall attractions, amenities, accessibilities, human resources, and prices are satisfactory in the eyes of tourists.Contribution — This study contributes some recommendations to managers to develop this destination based on constructive criticism and suggestions from millennial tourists.